Random process from the class V(φ,ψ): exceeding a curve - Yamnenko, R.; Vasylyk, O. (Інститут математики НАН України, 2007)
Random processes from the class V (φ, ψ) which is more general than the class of ψ-sub-Gaussian random process. The upper estimate of the probability that a random process from the class V (φ, ψ) exceeds some function is obtained. The results are applied to generalized process of fractional Brownian motion.